Criatividade na práxis arte-educadora escolar na educação infantil - Thompson, Francysmeyre Rodrigues (2024)
This research addresses creativity as a methodological bias in the praxis of art educators in early childhood education. Seeking to understand whether the presence of creativity in educational artistic practices in early childhood education, with the aim of understanding whether the mediated by the art educator promote or inhibit a creative environment. The role of art in the education of young children is highlighted as a means of promoting creativity and individual expression, which are fundamental for their integral development. Also the complexity of relating the child's development with creative stimuli, but the importance of understanding the general dynamics of the art-educational process is emphasized. The proposed methodology involves three stages: selection of the research field based on the pedagogical projects of art teachers, field observation for data collection and semi-structured interviews with teachers. The research is based on a qualitative approach, considering the child as an active social agent. Teachers' conceptions of creativity and their practical application are investigated. The data were analyzed using, as scientific methods, discourse analysis and analysis of data collected in the field. The conclusions obtained indicate that creative methods foster a more creative educational environment, stimulating children in their creativity